2000
DOI: 10.1042/0264-6021:3510403
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of human tensin

Abstract: Tensin is a focal-adhesion molecule that binds to actin filaments and interacts with phosphotyrosine-containing proteins. To analyse tensin's function in mammals, we have cloned tensin cDNAs from human and cow. The isolated approx. 7.7-kb human cDNA contains an open reading frame encoding 1735 amino acid residues. The amino acid sequence of human tensin shares 60% identity with chicken tensin, and contains all the structural features described previously in chicken tensin. This includes the actin-binding domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
62
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 14 publications
3
62
0
Order By: Relevance
“…Tensin family members have been shown to be downregulated in various cancer cells 14,19 ; however, variant 3, the smallest isoform of tensin2 and lacking the characteristic C1 domain in the N terminal, was capable of promoting cell migration. 16 In the present study, we found that variant 3 was overexpressed in human HCC tissue compared with the corresponding nontumorous liver tissue (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tensin family members have been shown to be downregulated in various cancer cells 14,19 ; however, variant 3, the smallest isoform of tensin2 and lacking the characteristic C1 domain in the N terminal, was capable of promoting cell migration. 16 In the present study, we found that variant 3 was overexpressed in human HCC tissue compared with the corresponding nontumorous liver tissue (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…13 Expression of human tensin1 was shown to be down-regulated in prostate and breast cancer cell lines. 14 Induction of tensin1 by cancer chemopreventive agent contributes to the anti-invasive activity of cancer cells. 15 Very recently, other structurally related tensin family members have been identified.…”
mentioning
confidence: 99%
“…Tensin2 is a member of tensin family, a focal-adhesion-molecule that stabilizes F-actin by binding to -integrin [4], as did -actinin4 (ACTN4) [21]. Of interest, a loss of tensin2 acts as a switch to trigger cell migration [27].…”
Section: Discussionmentioning
confidence: 99%
“…8A) (5, 19 -22). PTEN is a homolog of tensin (23,24). Since the amino terminus of tensin interacts with actin and within this region tensin shares sequence homology with PTEN, PTEN is a putative actin cytoskeleton-associated molecule.…”
Section: Inhibition Of Akt Activity Restores Sensitivity Of Pten Nullmentioning
confidence: 99%